Optimization of the Patrol Unit of the Samapta Unit in Preventing the Circulation of Alcoholic Beverages in the Jurisdiction of Polresta Surakarta - Naomi Shofura (Akademi Kepolisian Republik Indonesia, 2023)
The circulation of liquor is a problem which is often found in the jurisdiction of Surakarta Resort Police. The lack of intelligent information and the awareness of society to report the liquor distribution activities caused the liquor dealers and drinkers dared to do the action. In 2022, still increased as in previous years. The purpose of this writing is to describe and analyze the implementation and form of optimization Samapta Patrol Unit of in preventing the circulation of liquor in the jurisdiction of Surakarta Resort Police. The type of research used is research with a qualitative approach with descriptive analysis methods. This method describes the factual conditions that exist in the field and is analyzed using related theories. The theory that the writer uses is POAC management theory and Organizational Resource theory. The author also uses the concept of optimization and patrolling. In order to find out the causes and solutions to existing problems, the author carried out research in the jurisdiction of the Surakarta Resort Police. From theresults of the study, Samapta Patrol Unit is still not optimal in carrying out patrols to prevent the circulation of liquor in the jurisdiction of the Surakarta Resort Police. It was found that there were still deficiencies in the planning, organization, actuating, and controlling of the Patrol Unit and the aspects of human resources, budget, facilities and infrastructure and methods of conducting patrols were not yet optimal. The problems in this final project are solved by using theories and concepts in accordance with the hope that the Samapta Patrol Unit can be optimal and the number of liquor circulation in the jurisdiction of the Surakarta Resort Police can be reduced.